Development of nonlinear model for plug flow reactor process - Ahmad Akmal, Wahamid (2010)
Plug Flow Reactor are wildly use in chemical industries. The advantages of PFR reactor is Plug flow reactors have a high volumetric unit conversion and run for long periods of time without maintenance. The control of Plug Flow Reactor process a problem frequently encountered in the chemical industries. Controlling Plug Flow Reactor in chemical industries is very challenging because of the time varying and nonlinear characteristics of the Plug Flow Reactor processes. Nonlinear model of Plug flow reactor (PFR) process model is used to estimate the key unit operation variables when using a continuous tubular reactor to reach a specified output. In this paper gives an overview in selecting the best model in developing a nonlinear model for plug flow reactor. The steps in developing nonlinear model for plug flow reactor are developing of mathematical model in first principal including simulate under steady state and unsteady state condition, validation the mathematical model through an experimental. This model used reaction of ethyl acetate and sodium hydroxide to perform saponification for simulating the behavior of a simple Plug Flow Reactor process in a time. The mathematical model based on first principles is developed then, the model equation is solving in MATLAB environment by doing algorithm for this process. The program for Plug Flow Reactor system is created and this program known as nonlinear fundamental model. Two models were developed in this step in for comparison. The result from the MATLAB simulation program is compared with experimental results which have been selected from two difference method to validate the fundamental model. The result showed that the different between the model and experiment result is around 1-37%. As conclusion, the suitable nonlinear model for PFR system has been developed and analyses have been carried out to check the compatibility of the model.